Dietary intake of the water-soluble vitamins B1, B2, B6, B12 and C in 10 countries in the European Prospective Investigation into Cancer and Nutrition. - Olsen, A; Halkjaer, J; Gils, v; Buijsse, B; Verhagen, H; Jenab, M; Boutron-Ruault, M; Ericson, U; Ocké, M; Peeters, P; Touvier, M; Niravong, M; et al. (2009)
OBJECTIVES: To describe the intake of vitamins thiamine (B1), riboflavin (B2), B6 (pyridoxine), B12 (cobalamine) and C (ascorbic acid) and their food sources among 27 centres in 10 countries participating in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. METHODS: Between 1995 and 2000, 36 034 persons aged between 35 and 74 years were administered a standardized 24-h dietary recall using a computerized interview software programme (EPIC-SOFT). Intakes of the four B vitamins and vitamin C were estimated using the standardized EPIC Nutrient Database (ENDB). Mean intakes were adjusted for age and weighted by season and day of recall. RESULTS: Intake of B vitamins did not vary considerably between centres, except in the UK health-conscious cohort, in which substantially higher intakes of thiamine and lower intakes of vitamin B12 were reported compared with other centres. Overall, meat was the most important contributor to the B vitamins in all centres except in the UK health-conscious group. Vitamin C showed a clear geographical gradient, with higher intakes in the southern centres as compared with the northern ones; this was more pronounced in men than in women. Vegetables and fruits were major contributors to vitamin C in all centres, but juices and potatoes were also important sources in the northern centres. CONCLUSIONS: This study showed no major differences across centres in the mean intakes of B vitamins (thiamine, riboflavin, B6, B12), whereas a tendency towards a north-south gradient was observed for vitamin C.